Zircon U-Pb and Hf isotopic constraints on the genesis of a post-kinematic S-type Variscan tin granite: the Logrosán cupola (Central Iberian Zone) - Chicharro, Eva; Villaseca, Carlos; Valverde-Vaquero, Pablo; Belousova, Elena; López-García, José Ángel (Journal of Iberian Geology, 2014)
The Variscan orogeny produced widespread granites along the European Variscan belt. In relation to crustal thickening, post-collisional multiple tin-bearing highly fractionated S-type leucogranites were emplaced. The Logrosán granite represents one of those granitic bodies and is a focus of this study. The Logrosán granite is located in the Central Extremadura Batholith (CEB), within the Central Iberian Zone (CIZ) and was emplaced during post kinematic stages of the Variscan orogeny at ca. 308 Ma, as determined by combined ID-TIMS U–Pb and LA-ICPMS geochronology. The granitic body intruded the metasedimentary Schist Greywacke Complex (SGC) of Neoproterozoic age. A moderately evolved medium- to coarse-grained two mica leucogranite (Main unit) and some highly evolved aplitic or microporphyritic units (evolved units) are distinguishable on the basis of their petrography and whole rock geochemistry. Initial 87Sr/86Sr ratios vary from 0.7134 to 0.7311, whereas initial εNd shows a restricted range from -4.3 to -4.0 and εHf(t) ranges from +2.0 to -4.6 for Variscan-age zircons. Inherited zircons exhibit mostly Neoproterozoic ages and juvenile Hf-isotope composition (eHf up to +14.6), analogous to that of zircons from the SGC metasediments. The available geological, geochronological, geochemical and isotopic data allow to propose the partial melting of heterogeneous Neoproterozoic metasedimentary material, similar to the outcropping SGC, for the genesis of the Logrosán granite.